2006
DOI: 10.1038/labinvest.3700460
|View full text |Cite
|
Sign up to set email alerts
|

Self-antigen recognition by TGFβ1-deficient T cells causes their activation and systemic inflammation

Abstract: To investigate whether the multifocal inflammatory disease in TGFβ1-deficient mice is caused by self-antigen (self-Ag)-specific autoreactive T cells, or whether it is caused by antigen independent, spontaneous hyperactivation of T cells, we have generated Tgfb1 −/− and Tgfb1 −/− Rag1 −/− mice expressing the chicken OVA-specific TCR transgene (DO11.10). On a Rag1-sufficient background, Tgfb1 −/− DO11.10 mice develop a milder inflammation than do Tgfb1 −/− mice, and their T cells display a less activated phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…This underscores the vital, nonredundant role played by TGF-␤1 in regulating the response of CD4 ϩ T cells to self-Ags presented in the periphery. In support of this, restricting the TCR repertoire available to CD4 ϩ T cells through expression of a transgenic TCR prevents the development of inflammation and end-organ damage in TGF-␤1 Ϫ/Ϫ mice (9,10). Along with the current work, these data strongly suggest that the inflammatory pathology in TGF-␤1 Ϫ/Ϫ mice results from the interaction of autoreactive CD4 ϩ T cells with self-Ags.…”
Section: Tgf-␤1 Regulates Ag-specific Peripheral Cd4 ϩ T Cell Responsessupporting
confidence: 76%
See 1 more Smart Citation
“…This underscores the vital, nonredundant role played by TGF-␤1 in regulating the response of CD4 ϩ T cells to self-Ags presented in the periphery. In support of this, restricting the TCR repertoire available to CD4 ϩ T cells through expression of a transgenic TCR prevents the development of inflammation and end-organ damage in TGF-␤1 Ϫ/Ϫ mice (9,10). Along with the current work, these data strongly suggest that the inflammatory pathology in TGF-␤1 Ϫ/Ϫ mice results from the interaction of autoreactive CD4 ϩ T cells with self-Ags.…”
Section: Tgf-␤1 Regulates Ag-specific Peripheral Cd4 ϩ T Cell Responsessupporting
confidence: 76%
“…The majority of CD4 ϩ T cells in the liver and spleen from TGF-␤1 Ϫ/Ϫ mice express low levels of CD62 ligand (CD62L) 3 and high levels of CD44 and VLA-4, a surface expression profile consistent with TCR activation (4), although LPS alone can also induce similar T cell surface expression profiles (8). Evidence in support of the specific Ag model has been published recently; experimentally restricting the TCR repertoire available to CD4 ϩ T cells in TGF-␤1 Ϫ/Ϫ mice, through breeding of the TGF-␤1 Ϫ/Ϫ mouse with the OVA-specific DO11.10 TCR-transgenic mouse, prevented the development of T cell activation and tissue pathology (9,10). Further implicating a pathologic role for self-Ags, TGF-␤1 Ϫ/Ϫ mice raised in germfree conditions nevertheless develop end-organ inflammatory pathology, indicating that the presence of intestinal microflora is not necessary for disease (11).…”
mentioning
confidence: 99%
“…These data suggest that TGFβ1-deficient T cells do not require co-stimulatory signals through CD28 for their activation and autoimmune response [2]. Recently, we demonstrated, in Tgfb1 −/− mice, that elimination of self-antigen-reactive TCR-bearing T cells by genetic combination strongly inhibits activation of T cells and eliminates inflammation [33].We and others have also shown, using TCR-transgenic mice, that T reg -cell generation and maintenance in the periphery is not TGFβ1 dependent [39] (R. Bommireddy et al, unpublished). This suggests that TGFβ1 is important for the prevention of self-reactive T-cell activation, T reg -cell suppressor function or both.…”
Section: Phenotypes Of Tgfβ1-deficient Micementioning
confidence: 96%
“…They have also found that TGFβ1-deficient T reg cells fail to inhibit IFN production and T-cell activation in vivo and in vitro and also fail to protect mice from developing colitis in the adoptive-transfer model of colitis [42]. TGFβ1-independent T reg cells are unlikely to induce dominant tolerance because Tgfb1 −/− mice die at approximately weaning age from multi-organ autoimmunity [2,33].…”
Section: Tgfβ Function In T Reg Cellsmentioning
confidence: 99%
See 1 more Smart Citation